Simulating Transport of Soft Matter in Micro/Nano Channel Flows with Dissipative Particle Dynamics. Issue 2 (3rd December 2018) - Xu, Ziyang; Yang, Ye; Zhu, Guolong; Chen, Pengyu; Huang, Zihan; Dai, Xiaobin; Hou, Cuiling; Yan, Li‐Tang
Abstract: The flow‐induced transport of various soft matter systems through a fluidic channel has recently attracted great interest due to its significance ranging from the understanding of several chemical and biological processes to potential industrial and technical applications. Dynamic simulation and modeling can yield an insight into the detailed conformational, dynamical, and transport properties of soft matter systems, which is necessary to understand the transport properties of biological macromolecules in living organisms. As a mesoscopic particles‐based simulation technique, dissipative particle dynamics (DPD) has quickly been adopted as a promising approach for simulating dynamic and rheological properties of simple and complex fluids as well as the events taking place inside the fluidic channels. Here, the DPD method widely used in predicting the channel flow containing various soft matter systems is reviewed. The general aspect and basic formulations of DPD are introduced, and different boundary conditions are presented for wall‐bounded flows. In addition, the models based on DPD developed to simulate flow‐induced transport through fluidic channels for some typical soft matter systems are discussed, including red blood cells, vesicles, polymers, and biomacromolecules. Finally, the future directions to signify the framework in enhancing the design of novel functional systems and beyond are discussed. Abstract : Applications of dissipative particle dynamics (DPD) in flow‐induced transport of various soft matter systems through a fluidic channel are summarized, with a discussion on the future directions to signify the framework in enhancing the design of novel functional systems and beyond.